OPTIMIZING VIDEO IN ZOOM MEETINGS TO IMPROVE EFL STUDENTS' SPEAKING PERFORMANCE - Sunjayanto Masykuri, Edi (Universitas Muhammadiyah Metro, 2023)
Studies on improving speaking during the pandemic have been reported numerous. However, few did report using shortcut videos. The current study discusses how EFL students benefit from shortcut videos to improve their speaking skills during the pandemic 19. The subjects of this research were second semester-grade-student at Universitas Muhammadiyah Purworejo. The research was an online class and used a mixed method. The qualitative data are obtained by making the media for material; then evaluation uses online apps based on Android. The researchers observed students' activity by watching shortcut videos and answering the online quiz. The videos were shared through Zoom apps to help the learners to develop their speaking skills, especially in grammar, vocabulary, pronunciation, expressions, and fluency. The findings are that the students can learn English better in real situations. They got a suitable strategy for speaking English using shortcut videos without boredom. The students speaking skills were measured; the mean score before the video was 54.17, and the mean score after the video was 70.24. Therefore, there was a significant improvement in speaking skills after using shortcut video with Zoom apps. The study implies that teaching speaking needs creativity by employing digital resources.